Investigation of the Antioxidant, Antibacterial, and Antifungal Activities of the Leaf Extract Fractions of Sphagneticola trilobata L. Pruski Collected in Da Nang - Thi Thu Trang, Nguyen; Thi Khanh Hoa, Vo; Thi Kim Ngoc, Nguyen; Que Huong, Tran; Thi Thu Nga, Tran (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 1DO - 10.25073/2588-1132/vnumps.4718, 2025)
Sphagneticola trilobata L. Pruski – Asteraceae, is an introduced species, that grows wild and has strong growth ability. The study was conducted to determine the polyphenol content and biological activity of the extract fractions from leaves of S. trilobata . Total polyphenol content was determined by Follin Ciocalteu reagent, antioxidant activity was determined by DPPH free radical scavenging, and antimicrobial activity against S. aureus and C. albicans was determined by the agar disk diffusion method. The results showed that the polyphenol content ranged from 2.95 to 45.83 mg GAE/g and antioxidant activity with IC 50 values ​​ranged from 4.51 to 856.93 μg/mL. The inhibition zone diameters for S. aureus and C. albicans ranged from 9.70 to 22.30 mm and 8.0 to 13.53 mm, respectively. The ethyl acetate fraction had the highest polyphenol content and antioxidant. The ethyl acetate and n- hexane fractions exhibited equal antibacterial activities, while the chloroform fraction showed the strongest antifungal activity in the tested samples.